Haplodendron buzwilsoni gen. nov., sp. nov., the first record of Haplomunnidae from the southern Indo-Pacific (Isopoda: Asellota) - Just, Jean (Zootaxa, 2003)
A new genus and a new species, Haplodendron buzwilsoni, from the southeastern Australian mid bathyal are described. This is the first record of the family in the Southern Hemisphere IndoPacific. Diagnostic characters of the new genus are compared with those of other genera in the family. The possible significance of the joint possession, between the new genus and Dendrotion (Dendrotiidae), of a stalk carrying the antennulae and antennae is discussed. New observations on male reproductive structures are made.